Rules of Roots Combined - Examples, Exercises and Solutions

Question Types:
Applying Combined Exponents Rules: Applying the formulaApplying Combined Exponents Rules: Calculating powers with negative exponentsApplying Combined Exponents Rules: Complete the equationApplying Combined Exponents Rules: converting Negative Exponents to Positive ExponentsApplying Combined Exponents Rules: Factoring Out the Greatest Common Factor (GCF)Applying Combined Exponents Rules: FactorizationApplying Combined Exponents Rules: Identify the greater valueApplying Combined Exponents Rules: More than one unknownApplying Combined Exponents Rules: Multiplying Exponents with the same baseApplying Combined Exponents Rules: Number of termsApplying Combined Exponents Rules: A power lawApplying Combined Exponents Rules: Presenting powers in the denominator as powers with negative exponentsApplying Combined Exponents Rules: Presenting powers with negative exponents as fractionsApplying Combined Exponents Rules: Presenting powers with negative exponents as fractionsApplying Combined Exponents Rules: MonomialApplying Combined Exponents Rules: Single VariableApplying Combined Exponents Rules: TrinomialApplying Combined Exponents Rules: BinomialApplying Combined Exponents Rules: Two VariablesApplying Combined Exponents Rules: Using laws of exponents with parametersApplying Combined Exponents Rules: Using multiple rulesApplying Combined Exponents Rules: Using the laws of exponentsApplying Combined Exponents Rules: Using variablesApplying Combined Exponents Rules: Variable in the base of the powerApplying Combined Exponents Rules: Variable in the exponent of the powerApplying Combined Exponents Rules: Variables in the exponent of the powerApplying Combined Exponents Rules: Worded problemsApplying Combined Exponents Rules: The power of zeroRules of Roots Combined: Applying the formulaRules of Roots Combined: Identify the greater valueRules of Roots Combined: Number of termsRules of Roots Combined: Same base and different indicatorRules of Roots Combined: Solving the equationRules of Roots Combined: Using multiple rulesRules of Roots Combined: Using variables

Understanding the combination of powers and roots is important and necessary.

First property:
a=a12\sqrt a=a^{ 1 \over 2}
Second property:
amn=amn\sqrt[n]{a^m}=a^{\frac{m}{n}}
Third property:
(a×b)=a×b\sqrt{(a\times b)}=\sqrt{a}\times \sqrt{b}

Fourth property:
ab=ab\sqrt{\frac{a}{b}}=\frac{\sqrt{a}}{\sqrt{b}}

Fifth property:  
amn=an×m\sqrt[n]{\sqrt[m]{a}}=\sqrt[n\times m]{a}

Suggested Topics to Practice in Advance

  1. Square root of a product
  2. Square root of a quotient
  3. Square Roots

Practice Rules of Roots Combined

Examples with solutions for Rules of Roots Combined

Exercise #1

Solve the following problem:

(34)×(32)= \left(3^4\right)\times\left(3^2\right)=

Video Solution

Step-by-Step Solution

In order to solve this problem, we'll follow these steps:

  • Step 1: Identify the base and exponents

  • Step 2: Use the formula for multiplying powers with the same base

  • Step 3: Simplify the expression by applying the relevant exponent rule

Now, let's work through each step:

Step 1: The given expression is (34)×(32) (3^4) \times (3^2) . Here, the base is 3, and the exponents are 4 and 2.

Step 2: Apply the exponent rule, which states that when multiplying powers with the same base, we add the exponents:
am×an=am+n a^m \times a^n = a^{m+n}

Step 3: Using the rule identified in Step 2, we add the exponents 4 and 2:
34×32=34+2=36 3^4 \times 3^2 = 3^{4+2} = 3^6

Therefore, the simplified form of the expression is 36 3^6 .

Answer

36 3^6

Exercise #2

Choose the largest value

Video Solution

Step-by-Step Solution

Let's begin by calculating the numerical value of each of the roots in the given options:

25=516=49=3 \sqrt{25}=5\\ \sqrt{16}=4\\ \sqrt{9}=3\\ We can determine that:

5>4>3>1 Therefore, the correct answer is option A

Answer

25 \sqrt{25}

Exercise #3

2423= \frac{2^4}{2^3}=

Video Solution

Step-by-Step Solution

Let's keep in mind that the numerator and denominator of the fraction have terms with the same base, therefore we use the property of powers to divide between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it in the problem:

2423=243=21 \frac{2^4}{2^3}=2^{4-3}=2^1 Remember that any number raised to the 1st power is equal to the number itself, meaning that:

b1=b b^1=b Therefore, in the problem we obtain:

21=2 2^1=2 Therefore, the correct answer is option a.

Answer

2 2

Exercise #4

Simplify the following equation:

53×24×52×23= 5^3\times2^4\times5^2\times2^3=

Video Solution

Step-by-Step Solution

Let's simplify the expression 53×24×52×23 5^3 \times 2^4 \times 5^2 \times 2^3 using the rules for exponents. We'll apply the product of powers rule, which states that when multiplying like bases, you can add the exponents.

  • Step 1: Focus on terms with the same base.
    Combine 53 5^3 and 52 5^2 . Since both terms have the base 55, we apply the rule am×an=am+na^m \times a^n = a^{m+n}: 53×52=53+2=55 5^3 \times 5^2 = 5^{3+2} = 5^5

  • Step 2: Combine 24 2^4 and 23 2^3 . Similarly, for the base 22: 24×23=24+3=27 2^4 \times 2^3 = 2^{4+3} = 2^7

After simplification, the expression becomes:
55×27 5^5 \times 2^7

Answer

55×27 5^5\times2^7

Exercise #5

Solve the following exercise:

24= \sqrt{\frac{2}{4}}=

Video Solution

Step-by-Step Solution

Let's simplify the expression, first we'll reduce the fraction under the square root:

24=12= \sqrt{\frac{2}{4}}= \\ \sqrt{\frac{1}{2}}=

We'll use two exponent laws:

A. Definition of root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

B. The power law for powers applied to terms in parentheses:

(ab)n=anbn \big(\frac{a}{b}\big)^n=\frac{a^n}{b^n}

Let's return to the expression we received, first we'll use the law mentioned in A and convert the square root to a power:

12=(12)12= \sqrt{\frac{1}{2}}=\\ \big(\frac{1}{2}\big)^{\frac{1}{2}}=

We'll continue and apply the power law mentioned in B, meaning- we'll apply the power separately to the numerator and denominator, in the next step we'll remember that raising the number 1 to any power will always give the result 1, and in the fraction's denominator we'll return to the root notation, again, using the power law mentioned in A (in the opposite direction):

(12)12=112212=12 \big(\frac{1}{2}\big)^{\frac{1}{2}}= \\ \frac{1^{\frac{1}{2}}}{2^{\frac{1}{2}}}=\\ \boxed{\frac{1}{\sqrt{2}}}\\ Let's summarize the simplification of the given expression:

24=12=112212=12 \sqrt{\frac{2}{4}}= \\ \sqrt{\frac{1}{2}}= \\ \frac{1^{\frac{1}{2}}}{2^{\frac{1}{2}}}=\\ \boxed{\frac{1}{\sqrt{2}}}\\ Therefore, the correct answer is answer D.

Answer

12 \frac{1}{\sqrt{2}}

Exercise #6

Solve the following exercise:

161= \sqrt{16}\cdot\sqrt{1}=

Video Solution

Step-by-Step Solution

Let's start by recalling how to define a root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

Next, we will remember that raising 1 to any power will always yield the result 1, even the half power of the square root.

In other words:

161=1612=16112=161=16=4 \sqrt{16}\cdot\sqrt{1}= \\ \downarrow\\ \sqrt{16}\cdot\sqrt[2]{1}=\\ \sqrt{16}\cdot 1^{\frac{1}{2}}=\\ \sqrt{16} \cdot1=\\ \sqrt{16} =\\ \boxed{4} Therefore, the correct answer is answer D.

Answer

4 4

Exercise #7

Solve the following exercise:

12= \sqrt{1}\cdot\sqrt{2}=

Video Solution

Step-by-Step Solution

Let's start by recalling how to define a square root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

Next, we remember that raising 1 to any power always gives us 1, even the half power we got from converting the square root.

In other words:

12=122=1122=12=2 \sqrt{1} \cdot \sqrt{2}= \\ \downarrow\\ \sqrt[2]{1}\cdot \sqrt{2}=\\ 1^{\frac{1}{2}} \cdot\sqrt{2} =\\ 1\cdot\sqrt{2}=\\ \boxed{\sqrt{2}} Therefore, the correct answer is answer a.

Answer

2 \sqrt{2}

Exercise #8

Solve the following exercise:

301= \sqrt{30}\cdot\sqrt{1}=

Video Solution

Step-by-Step Solution

Let's start with a reminder of the definition of a root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

We will then use the fact that raising the number 1 to any power always yields the result 1, particularly raising it to the power of half of the square root (which we obtain by using the definition of a root as a power mentioned earlier).

In other words:

301=3012=30112=301=30 \sqrt{30}\cdot\sqrt{1}= \\ \downarrow\\ \sqrt{30}\cdot\sqrt[2]{1}=\\ \sqrt{30}\cdot 1^{\frac{1}{2}}=\\ \sqrt{30} \cdot1=\\ \boxed{\sqrt{30}}

Therefore, the correct answer is answer C.

Answer

30 \sqrt{30}

Exercise #9

9993= \frac{9^9}{9^3}=

Video Solution

Step-by-Step Solution

Note that in the fraction and its denominator, there are terms with the same base, so we will use the law of exponents for division between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} Let's apply it to the problem:

9993=993=96 \frac{9^9}{9^3}=9^{9-3}=9^6 Therefore, the correct answer is b.

Answer

96 9^6

Exercise #10

Reduce the following equation:

a2×a5×a3= a^2\times a^5\times a^3=

Video Solution

Step-by-Step Solution

To reduce the expression a2×a5×a3 a^2 \times a^5 \times a^3 , we will apply the product of powers property of exponents. This property states that when multiplying expressions with the same base, we add their exponents.

  • Step 1: Identify the exponents.
    The expression involves the same base a a with exponents: 2, 5, and 3.
  • Step 2: Add the exponents.
    According to the product of powers property, a2×a5×a3=a2+5+3 a^2 \times a^5 \times a^3 = a^{2+5+3} .
  • Step 3: Simplify the expression.
    Calculate the sum of the exponents: 2+5+3=10 2 + 5 + 3 = 10 . Therefore, the expression simplifies to a10 a^{10} .

Ultimately, the solution to the problem is a10 a^{10} . Among the provided choices, is correct: a10 a^{10} . The other options a5 a^5 , a8 a^8 , and a4 a^4 do not correctly reflect the sum of the exponents as calculated.

Answer

a10 a^{10}

Exercise #11

Simplify the following equation:

64×23×62×25= 6^4\times2^3\times6^2\times2^5=

Video Solution

Step-by-Step Solution

To simplify the equation 64×23×62×25 6^4 \times 2^3 \times 6^2 \times 2^5 , we will make use of the rules of exponents, specifically the product of powers rule, which states that when multiplying two powers that have the same base, you can add their exponents.

Step 1: Identify and group the terms with the same base.
In the expression 64×23×62×25 6^4 \times 2^3 \times 6^2 \times 2^5 , group the powers of 6 together and the powers of 2 together:

  • Powers of 6: 64×62 6^4 \times 6^2

  • Powers of 2: 23×25 2^3 \times 2^5

Step 2: Apply the product of powers rule.
According to the product of powers rule, for any real number a a , and integers m m and n n , the expression am×an=am+n a^m \times a^n = a^{m+n} .

Apply this rule to the powers of 6:
64×62=64+2=66 6^4 \times 6^2 = 6^{4+2} = 6^6 .

Apply this rule to the powers of 2:
23×25=23+5=28 2^3 \times 2^5 = 2^{3+5} = 2^8 .

Step 3: Write down the final expression.
Combining our results gives the simplified expression: 66×28 6^6 \times 2^8 .

Therefore, the solution to the problem is 66×28 6^6 \times 2^8 .

Answer

66×28 6^6\times2^8

Exercise #12

Insert the corresponding expression:

(x3)4= \left(x^3\right)^4=

Video Solution

Step-by-Step Solution

To simplify the expression (x3)4 (x^3)^4 , we'll follow these steps:

  • Step 1: Identify the expression: (x3)4 (x^3)^4 .
  • Step 2: Apply the formula for a power raised to another power.
  • Step 3: Calculate the product of the exponents.

Now, let's work through each step:

Step 1: We have the expression (x3)4 (x^3)^4 , which involves a power raised to another power.

Step 2: We apply the exponent rule (am)n=amn(a^m)^n = a^{m \cdot n} here with a=xa = x, m=3m = 3, and n=4n = 4.

Step 3: Multiply the exponents: 3×4=12 3 \times 4 = 12 . This gives us a new exponent for the base x x .

Therefore, (x3)4=x12(x^3)^4 = x^{12}.

Consequently, the correct answer choice is: x12 x^{12} from the options provided. The other options x6 x^6 , x1 x^1 , and x7 x^7 do not reflect the correct application of the exponent multiplication rule.

Answer

x12 x^{12}

Exercise #13

Simplify the following equation:

42×35×43×32= 4^2\times3^5\times4^3\times3^2=

Video Solution

Step-by-Step Solution

To simplify the given expression 42×35×43×32 4^2 \times 3^5 \times 4^3 \times 3^2 , we will follow these steps:

  • Step 1: Identify and group similar bases.

  • Step 2: Apply the rule for multiplying like bases.

  • Step 3: Simplify the expression.

Now, let's go through each step thoroughly:

Step 1: Identify and group similar bases:
We see two distinct bases here: 4 and 3.

Step 2: Apply the rule for multiplying like bases:
For base 4: Combine 424^2 and 434^3, using the rule am×an=am+na^m \times a^n = a^{m+n}.

Add the exponents for base 4: 2+3=5 2 + 3 = 5 , thus, 42×43=45 4^2 \times 4^3 = 4^5 .

For base 3: Combine 353^5 and 323^2, still using the same exponent rule.

Add the exponents for base 3: 5+2=7 5 + 2 = 7 , resulting in 35×32=37 3^5 \times 3^2 = 3^7 .

Step 3: Simplify the expression:
The simplified expression is 45×37 4^5 \times 3^7 .

Therefore, the final simplified expression is 45×37 4^5 \times 3^7 .

Answer

45×37 4^5\times3^7

Exercise #14

Solve the following exercise:

25x4= \sqrt{25x^4}=

Video Solution

Step-by-Step Solution

To simplify the given expression, we will use the following three laws of exponents:

a. Definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. Law of exponents for an exponent applied to terms in parentheses:

(ab)n=anbn (a\cdot b)^n=a^n\cdot b^n

c. Law of exponents for an exponent raised to an exponent:

(am)n=amn (a^m)^n=a^{m\cdot n}

We'll start by converting the fourth root to an exponent using the law of exponents mentioned in a.:

25x4=(25x4)12= \sqrt{25x^4}= \\ \downarrow\\ (25x^4)^{\frac{1}{2}}=

We'll continue, using the law of exponents mentioned in b. and apply the exponent to each factor in the parentheses:

(25x4)12=2512(x4)12 (25x^4)^{\frac{1}{2}}= \\ 25^{\frac{1}{2}}\cdot(x^4)^{{\frac{1}{2}}}

We'll continue, using the law of exponents mentioned in c. and perform the exponent applied to the term with an exponent in parentheses (the second factor in the multiplication):

2512(x4)12=2512x412=2512x2=25x2=5x2 25^{\frac{1}{2}}\cdot(x^4)^{{\frac{1}{2}}} = \\ 25^{\frac{1}{2}}\cdot x^{4\cdot\frac{1}{2}}=\\ 25^{\frac{1}{2}}\cdot x^{2}=\\ \sqrt{25}\cdot x^2=\\ \boxed{5x^2}

In the final steps, we first converted the power of one-half applied to the first factor in the multiplication back to the fourth root form, again, according to the definition of root as an exponent mentioned in a. (in the reverse direction) and then calculated the known fourth root of 25.

Therefore, the correct answer is answer a.

Answer

5x2 5x^2

Exercise #15

(35)4= (3^5)^4=

Video Solution

Step-by-Step Solution

To solve the exercise we use the power property:(an)m=anm (a^n)^m=a^{n\cdot m}

We use the property with our exercise and solve:

(35)4=35×4=320 (3^5)^4=3^{5\times4}=3^{20}

Answer

320 3^{20}

Topics learned in later sections

  1. Square Root Rules